Gas gain study of a large-size multilayer Micromegas. (December 2020) - Dubinin, F; Iengo, P; Sekhniaidze, G; Zhukov, K
Abstract: The results of the study of a large-size, multilayer Micromegas detector with X-ray source Cd-109 are discussed. The detector consists of 4 layers, each of them is a Micromegas detector with resistive anode and strip-based read-out structure. The gas volume of the chamber is split to 4 parts interconnected in 6 points. Results of the measurements of the gas gain curves and the 1st Townsend coefficient as well as the E_amp/E_drift characteristics are presented and discussed. The detector presented a non-negligible gas leak, affecting the reported results. The influence of the leak on operation of the module is estimated.